2018
DOI: 10.1186/s12967-018-1739-5
|View full text |Cite
|
Sign up to set email alerts
|

NovelmiRNA-25 inhibits AMPD2 in peripheral blood mononuclear cells of patients with systemic lupus erythematosus and represents a promising novel biomarker

Abstract: BackgroundSystemic lupus erythematosus (SLE) is a multisystemic autoimmune disease with various clinical manifestations. MicroRNAs (miRNAs) and immunometabolism are recognized as key elements in SLE pathogenesis; however, the relationship between miRNAs in peripheral blood mononuclear cells (PBMCs) and metabolism in SLE remains unclear.MethodsWe detected PBMC miRNA and mRNA profiles from 3 pooled SLE patients and 3 healthy controls (HCs) using next-generation sequencing, predicted miRNA targets in dysregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 45 publications
8
30
1
Order By: Relevance
“…However, five articles were excluded by reading their complete articles due to article types, seven studies lacked available data to construct a 2×2 table, and four articles lacked a comparison between SLE patients and healthy controls. Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, five articles were excluded by reading their complete articles due to article types, seven studies lacked available data to construct a 2×2 table, and four articles lacked a comparison between SLE patients and healthy controls. Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials.…”
Section: Search Resultsmentioning
confidence: 99%
“…Additionally, the ideal time for specimen acquisition was before treatment. Unfortunately, only two of the studies [17,31] involved in our meta-analysis indicated that blood samples were collected before treatment, while six studies [20,33,37,39,40,42] did not clarify when the specimens were obtained, five studies [18,19,21,36,41] stated that samples were collected during the period of treatments, and four articles [32,34,35,38] indicated that the time for specimen collection was after the patients had stopped treatments for a period of time. Thus, these differences in patient and blood collection time could cause inevitable bias to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is an autoimmune disease and its prevalence varies from approximately 20 to 70 per 100,000 people per year, and incidence rates for women are approximately ten times higher than those for men worldwide (1,2). More than 80% of patients with SLE present clinical manifestations such as nephritis, multisystem organ failure, or central nervous system disease.…”
Section: Introductionmentioning
confidence: 99%
“…Functional analyses further identified cellular process, metabolic process, regulation of signal transduction, and cell surface receptor signaling pathway to be important in the development of autoimmune diseases. In a previous research, we showed that mRNAs differentially expressed between SLE patients and HCs in PBMCs were also enriched in cellular process, metabolic process, and Wnt signaling pathway (Guo et al, 2018a). Immunometabolism in SLE involves dysregulation in many immune cells, including CD4+ T cells, dendritic cells, macrophages, and neutrophils (Morel, 2017).…”
Section: Discussionmentioning
confidence: 91%